Sarcomas of the head and neck in clinical material from Clinic of Cranio-Maxillofacial and Oncological Surgery of Medical University of Lodz - Grodecka, Joanna; Zielińska-Kaźmierska, Bogna; Arkuszewski, Piotr; Tyndorf, Marta (Contemporary Oncology/Współczesna Onkologia, 2007)
Sarcomas are the malignant neoplasms originating from mesenchymal tissue. They can arise from connective, vascular, muscular and other tissues. The most frequent localization is on the trunk and limbs, but in maxillofacial region they occur rarely and have worse survival prognosis. Initially they arise asymptomatically and painlessly. Radiological findings are also untypical. The best results of treatment are obtained by the combined therapy. Applying not only surgery but also chemiotherapy and radiotherapy in the treatment of patients with sarcomas enabled longer 5-years survival from 20% to almost 70%. We want to present 4 patients treated in the Department of Cranio- -Maxillofacial Surgery of the Medical University in Lodz during the recent years. There were 2 patients with chondrosarcomas, 1 with osteosarcomas and 1 with leyomiosarcoma.